2011
DOI: 10.1016/j.molcel.2011.08.041
|View full text |Cite
|
Sign up to set email alerts
|

RAM/Fam103a1 Is Required for mRNA Cap Methylation

Abstract: SummaryThe 7-methylguanosine cap added to the 5′ end of mRNA is required for efficient gene expression in eukaryotes. In mammals, methylation of the guanosine cap is catalyzed by RNMT (RNA guanine-7 methyltransferase), an enzyme previously thought to function as a monomer. We have identified an obligate component of the mammalian cap methyltransferase, RAM (RNMT-Activating Mini protein)/Fam103a1, a previously uncharacterized protein. RAM consists of an N-terminal RNMT-activating domain and a C-terminal RNA-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(156 citation statements)
references
References 25 publications
5
151
0
Order By: Relevance
“…Additionally, siRNA-mediated knockdown of RNMT greatly reduced the cap methyltransferase activity of cytoplasmic extracts, suggesting that RNMT is the predominant, if not only cap methyltransferase in the cytoplasm of mammalian cells. Nuclear RNMT exists as a heterodimer with RNMT-activating miniprotein (RAM, Gonatopoulos-Pournatzis et al , 2011), and we demonstrated that cytoplasmic RNMT also binds to RAM. Reduced cytoplasmic cap methyltransferase activity upon RAM knockdown indicated that RAM is a required cofactor for cytoplasmic RNMT.…”
Section: [Background]mentioning
confidence: 86%
“…Additionally, siRNA-mediated knockdown of RNMT greatly reduced the cap methyltransferase activity of cytoplasmic extracts, suggesting that RNMT is the predominant, if not only cap methyltransferase in the cytoplasm of mammalian cells. Nuclear RNMT exists as a heterodimer with RNMT-activating miniprotein (RAM, Gonatopoulos-Pournatzis et al , 2011), and we demonstrated that cytoplasmic RNMT also binds to RAM. Reduced cytoplasmic cap methyltransferase activity upon RAM knockdown indicated that RAM is a required cofactor for cytoplasmic RNMT.…”
Section: [Background]mentioning
confidence: 86%
“…9,10 RNMT has a catalytic core, which is homologous in structure and function to other eukaryotic cap methyltransferases. 11 In addition, RNMT contains an N-terminal noncatalytic domain, which is conserved in mammals but not in other eukaryotes (Fig.…”
Section: Regulation Of Mrna Cap Methylationmentioning
confidence: 99%
“…11 RAM also has a high-affinity RNA binding domain which may increase the rate of recruitment of transcripts in general or may have specificity for particular transcript motifs. 10,13 In human cells, RNMT-RAM is recruited via the N-terminal domain of RNMT to RNA pol II proximal to transcription initiation sites. 14,15 The RNMT N-terminal domain also impacts on cap methyltransferase activity.…”
Section: Regulation Of Mrna Cap Methylationmentioning
confidence: 99%
“…The human RNMT structure was released by the Structural Genomics Consortium (SGC; PDB: 3BGV), and has considerable similarity to Ecm1 (RMSD: 1.25 Å) (22). RNMT also has an activating subunit, RAM (RNMT-activating miniprotein) (23). Although homologues of RNMT are present in all eukaryotes, RAM is only present in vertebrates leading to interest in its mechanism of action and cellular function.…”
Section: Introductionmentioning
confidence: 99%
“…RAM consists of an N-terminal RNMT activation domain (residues 1–55), a central RNA binding domain (residues 56–90), and a C-terminal PY nuclear localisation domain (residues 91–118) (23,24). The RAM RNA binding domain is required for cell viability but not for RNMT activation, and therefore may select specific critical transcripts for enhanced methylation.…”
Section: Introductionmentioning
confidence: 99%